Eeg and Emg Alterations in Children With Chronic Renal Failure - Yazgan, Hamza; Özçay, Sevil (Fırat University, 2002)
Aim: To identify the changes of electroencephalography (EEG) and electromyography (EMG), and to assess the association between blood urea, creatinin, calcium levels, dialysis treatment and duration of illness. Material and Methods: Thirty children with chronic renal failure was involved in this study who were followed at the pediatric nephrology department of SSK Göztepe Teaching Hospital. During EEG and EMG measurements, none of the patients presented uremic or hypertensive encephalopathy. Serum urea, creatinin and calcium levels were synchronically evaluated. Results: Of the patients, 15 were female (50%), 15 were males (50%). The mean age of girls was 12.23 ± 2.9 years, while the mean age of boys was 11.23±3.62. 17 patients (56.6%) were undergoing hemodialysis treatment while 13 patients (43.4%) were at predialysis stage. 17 subjects (56.6%) had pathological EEG; of which 14 displayed slow diffuse wave pattern, and two of them revealed encephalopathy-associated changes. Finally, one of them had focal electrical discharge. Six cases (20%) presented full accordance with peripheral neuropathy and also exhibited a mild declination in the nerve conduction rate which probably resulted from motor and sensorial nerve fibers damage. Conclusions: The average duration of disease in cases with peripheric neuropathy was found to be 5 years. Additionally, neuropathy was not observed in patients who received dialysis treatment. We could not found statistically significant relationship between EEG and EMG pathology and blood urea, creatinin and calcium levels.

Amaç: Kronik böbrek yetmezliği olan çocuklarda elektroensefalografi (EEG) ve elektromyografik (EMG) değişiklikler ve bu değişikliklerin üre, keratinin, kalsiyum, diyaliz tedavisi ve hastalık süresi ile ilişkisini belirlemek. Materyal ve Metod: SSK Göztepe Eğitim ve Araştırma Hastanesi Çocuk Nefroloji Kliniğinde takip edilen kronik böbrek yetmezliği (KBY) tanısı almış toplam 30 hasta bu çalışma kapsamına alındı. EEG ve EMG ölçümleri sırasında hastalarda üremik ve hipertansif ensefalopati yoktu. Serum üre, kreatinin ve kalsiyumu eş zamanlı olarak değerlendirildi. Bulgular: Hastaların 15'i kız (%50) ve 15'i erkekti (%50). Kızların yaş ortalaması 12.23±2.9, erkeklerin ise 11.23±3.62 idi. Olgulardan 17'si (%56.6) hemodiyaliz tedavisi almakta 13'ü (%43.4) ise prediyaliz olgusu idi. On yedi olguda (%56.6) patolojik EEG saptandı ve bunlarında 14'ü diffüz yavaş dalga, ikisi ensefalopati ile uyumlu değişiklikler ve birisi ise fokal elektriksel deşarj şeklinde idi. Altı olgunun EMG'si (%20) periferik nöropati ile uyumlu ve alt ekstremitelerdeki motor ve duysal sinir liflerinin etkilenmesi sonucu sinir ileti hızında yavaşlama mevcuttu. Sonuç: Periferik nöropati saptanan KBY'li olgularda ortalama hastalık süresi beş yıl olarak bulundu ve diyaliz tedavisi alan hastalarda nöropati gözlenmedi. EEG ve EMG patolojisi ile üre, kreatinin ve kalsiyum değerleri arasında istatistiki olarak bir ilişki bulunamadı.
Kronik Böbrek Yetmezliği Olan Çocuklarda Eeg ve Emg Değişiklikleri